Public Trust Crisis in the Judicial System: An Institutional and Implementative Analysis - Girly Farsyadiva Althaira Nurahim; Nandang Sambas (Jurnal Smart Hukum (JSH), 2026)
Public trust is the primary foundation for the sustainability of the judicial legal system in a democratic rule-of-law state. A judicial system trusted by the public not only functions as a mechanism for dispute resolution and law enforcement but also serves as a source of state legitimacy in ensuring justice, legal certainty, and the protection of human rights. However, in recent decades, the judicial legal system in various countries, including Indonesia, has faced an increasingly pronounced crisis of public trust. This crisis is reflected in negative public perceptions regarding judicial independence, the integrity of law enforcement officials, and the quality of court decisions, which are considered not yet fully reflective of substantive justice. This study aims to analyze the institutional and implementative factors that contribute to the crisis of public trust in the judicial legal system. The research employs a normative juridical method with statutory and conceptual approaches, through an examination of legal norms, doctrines, and contemporary scholarly literature. The findings indicate that the public trust crisis stems from weak institutional integrity, low transparency and accountability, and the gap between legal norms and judicial practice. Therefore, strengthening institutional reform and improving the implementation of law enforcement are essential prerequisites for restoring public trust in the judicial legal sys